Blazan, Sladja (Ed.). (2021). Haunted Nature: Entanglements of the Human and the Nonhuman. - Jordan, Rebecca (Journal of Ecohumanism, 2023)
Blazan, Sladja (Ed.). (2021). Haunted Nature: Entanglements of the Human and the Nonhuman. Palgrave Macmillan. ISBN 978-3-030-81868-5.